Exploring shape and colors from existing silk scarf by integrating Chinese Dunhuang Mural elements to contemporary perception from historical evolution and cultural perspective in China - Md Yusoff, Irwan Syah; Alli, Hassan; Fei, Liu (Ponte Editora Lda., 2024)
Dunhuang murals are the world's oldest and most culturally rich world-class cultural treasure in China. How combining classical Dunhuang murals with new-era clothing and jewelry design is crucial for the inheritance and development of Dunhuang culture. Based on analyzing the line and shape architecture of Dunhuang murals, this study interprets the aesthetic attributes of Dunhuang murals' designs and further reveals the aesthetic attributes of Dunhuang murals' colors from the perspectives of color style and cultural connotations. Based on the above aesthetic and cultural factors, this study further analyzes the application practice and innovative principles of Dunhuang murals and proposes a method and artistic means of mural design reconstruction based on modern pragmatism. The research results indicate significant differences in the color and design styles of Dunhuang murals in different historical periods. The changes in the size of unit designs, the thickness of contour lines, and the changes in hue, brightness, and saturation in color in Dunhuang murals refer to the changes in the arrangement of designs in a fixed area. They not only serve to separate different mural contents for the sake of aesthetic decoration but also highlight the structural characteristics of the cave. The edge decoration designs created based on the structure itself will have more intuitive properties. In the process of designing Dunhuang mural empowering scarves, digital prints can be inputted into a computer through digital means, and then processed through a computer color separation printing system. Specialized software can directly spray various specialized dyes onto the silk fabric through the printing system, and then undergo later processing to obtain the required printing products on the material.